Against Hauerwas - Hobson, Theo (New blackfriars, 2007)
This essay questions the theological position developed by Stanley Hauerwas over three decades. It first traces the origins of his thought, and argues that the alliance of radical Reformation ecclesiology with postmodern philosophy leads to an intensely idealistic ecclesiology. Hauerwas's exaltation of particular communal practices is ultimately unreal, as he fails to locate these practices in a particular institution. Due to the unreality of his ecclesiology his attack on Christendom and Constantinianism lacks substance. In the end he undermines his own position by identifying the truth of Christianity with the concrete practices of a distinctive community that he cannot identify.